An Example of Machine Learning Applied in Additive Manufacturing - Douard, Amelina; Grandvallet, Christelle; Pourroy, Franck; Vignat, Frederic (2018 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2018)
Artificial Intelligence has become ubiquitous in many application sectors nowadays. One field, machine learning, has proved to be promising for industries as it can solve complex problems thanks to various methods and algorithms. The present article is an example of machine learning with EBM, a recent additive manufacturing technology. Several algorithms are tested onto the manufacturing of a part in order to check which results can extrapolate at the best the deformation risks vs the quality of the part to build. In this example, a few parameters of support structures are identified and are varied to observe the algorithms validity.